(untitled) (Annals of Medical Research, 2023)
Aim: Coeliac trunk and hepatic artery variations are not uncommon and may complicate surgery in patients with periampullary cancer. We aimed to assess the prevalence and types of variations of the coeliac trunk and hepatic arteries and their relationship with surgical complications in patients undergoing pancreatoduodenectomy. Materials and Methods: In this single-center study, we retrospectively reviewed the preoperative contrast-enhanced abdominal computed tomography scans of patients with periampullary cancer. Coeliac trunk branching with a particular focus on hepatic artery origin was assessed on arterial phase images. Results: The study included a total of 66 patients [39 (59.1%) men] with a mean age of 63.92±12.98 years. The most frequent tumor origin was the pancreatic head, seen in 41 (62.1%) cases, followed by the ampulla in 15 (22.7%), distal common bile duct in seven (12.1%), and colon tumors invading the duodenum in two (3%). Arterial variations were observed in 15 (22.7%) cases. Total perioperative complications occurred in 14 cases (13 fistulas and one hematoma). There was a higher rate of complications in the group with variations (n=5, 33.3%) compared to the group without variations (n=9, 17.6%), but it was not statistically significant (p=0.496). Conclusion: Coeliac trunk and hepatic arterial variations are very common but do not seem to significantly increase complications in patients undergoing pancreatoduodenectomy.